The Reversal of Gender Roles: Girl Gangs in Rebecca Prichard’s Yard Gal - Kalavská, Petra (My University, 2023)
The article concentrates on the dramatic work by the younger generation of British women who started writing in the 1990s and explains why their plays were not initially seen to fit into the category of womenʼs drama. It considers the changes in feminist thinking and the reasons why second-wave feminism seems to have lost its edge and became regarded as insufficient by the new generation. Even though Yard Gal (1998) by Rebecca Prichard (1971) differs from the feminist plays written in the 1980s, the article suggests that it is a subtly feminist and implicitly political play as it condemns apolitical power feminism which does not consider the disadvantaged and socially deprived. The play criticises ʻgirl powerʼ and uncovers the deleterious effects of postfeminism as it does not aim to transform the social reality of those who are on the edge of British society.
Záměna rolí: Dívčí gangy v Yard Gal od Rebeccy Prichard
Keywords: In-Yer-Face Theatre; postfeminism; power feminism; Rebecca Prichard; Yard Gal; In-Yer-Face divadlo; postfeminismus; Rebecca Prichard; Yard Gal